Canailicious / Mohamad Ishaq Mohd Tarmizi ... [et al.] - Mohd Tarmizi, Mohamad Ishaq; Abd Razak, Nurul Hafizah; Nor Mohemmad, Nur Syahirah; Ikhsan, Intan Sharina; Md Salleh, Siti Khadijah (2014)
Canai Licious is a business that is develops for a food industry which focuses on the Roti Canai as the main foods. The location of the business is at No. 5 Jalan SILC, Nusajaya Square 2, 80000 Johor Bharu, Johor DarulTakzim. The business basically provide people with variety of Roti Canai in different flavored like chocolate, raisins, peanut butter, strawberry, blueberry, and banana. The business serves them with frozen and fresh cooking of Roti Canai. Even though there is lots of business that serve frozen food, Canai Liciuos have its own specialty that can survive in such a long time in a the market. Furthermore, Roti Canai is one of the familiarand favorite dishes in Malaysia notonly among adults but also teenagers, elders, kids and family. Due to the time limited in preparing heavy meals especially for those who are working, this business choose to provide Malaysians with this product as to chelp them serve their family with simple and tasty food within short time. So that people can have simple and at the same time tasty food with their family easily. Moreover, the business is purposely to provide people who like to eat Roti Canai with variety flavored like chocolate, raisins; durian, strawberry, blueberry, and banana that maintain in the original taste of it and get all the nutrients needed for a good health. Therefore, this product can be imported to other countries beside Malaysia. This is because this product is Bumiputera's product with Halal confirmation. This business has its own strength which can be accepted by all people which always find for a good and Halal food.